Judicial Reasoning in Appellate Sentencing for Major Corruption Cases - Diah Septi Haryani; Mulyadi Mulyadi (Jurnal Daulat Hukum, 2025)
This study aimed to examine the judicial reasoning behind the enhancement of an appellate sentence in a major corruption case in Indonesia and to assess whether the judges’ considerations aligned with the principles of due process of law, proportionality, and legal certainty. The research method used was a normative juridical approach employing statutory, case, and comparative analyses. Data were obtained through library research involving primary legal materials, secondary literature, and tertiary references, and were analyzed qualitatively through a descriptive-analytical technique. The novelty in this research lies in its focused examination of appellate judges’ authority to impose heavier sentences in corruption cases, particularly by identifying the juridical foundation used to justify sentence enhancement and by evaluating its coherence with fundamental principles of criminal procedure. Unlike previous studies that primarily discuss corruption sentencing disparities or political influences on judicial decisions, this research provides a detailed analysis of how appellate judicial reasoning functions as a mechanism to uphold substantive justice. Based on the research, it was concluded that the appellate judges grounded their decision on legally valid evidence and carefully weighed both aggravating and mitigating factors, including the scale of state losses, societal impact, and the defendant’s cooperative conduct. The enhanced sentence was consistent with proportionality, due process, and legal certainty, and represents an important precedent for strengthening judicial integrity and advancing reform within Indonesia’s criminal justice system.